Forms of Motor Activity of Students - Kholova Shakhnoza Mardonovna (Central Asian Journal of Theoretical and Applied Science, 2022)
This article discusses the forms of physical activity. Maintaining a healthy lifestyle involves the use of various methods, and the use of an individual, carefully selected plan. This plan should take into account the physiological and psychological characteristics of a particular person seeking to improve his condition.